Multi-scale pore structure characteristics and main controlling factors analysis of Longtan formation shale in Northwest Guizhou - Huang, Yuqi; Zhang, Jinchuan; Zhang, Peng; Tang, Xuan; Yang, Junwei (Frontiers in Earth Science, 2023)
Marine-continental transitional shale strata are widely distributed in China and have high shale gas resource potential. the Longtan shales are a typical marine-continental transitional coal-bearing shale system in Northwest Guizhou. The multi-scale pore structure characteristics were studied using different experimental methods and calculation models. The macropores (≥100nm) are mainly inorganic with a fractal dimension D1 between 2.8628-3.2057, indicating the macropore structure is relatively complex. The proportion of the macropores in total pores is not high, and the content of brittle minerals and pyrite mainly controls its structure. Among the mesopores (50-100nm), inorganic pores are still the primary pore type, but the proportion of organic pores increases. The fractal dimension D2 is between 2.2125-2.3016. It has medium complexity, and the proportion in the total pores is slightly higher than that of macropores. The influence of organic matter abundance on mesopore structure is greater than that in macropore because of the increase in the proportion of organic pores, making the controlling controlling mechanism of mesopore structure is more complicated. Mini-micro (< 50nm) pores are mainly organic pores. The fractal dimension D3 (fractal dimension of mini-micropores under low relative pressure, P/P0≤0.5) ranges between 2.6709-2.8648, and D3' (fractal dimension of mini-micropores under high relative pressure, P/P0＞0.5) ranges between 2.6661-2.9256, indicating complex pore structures and rough surfaces. Mini-micropore accounts for the highest proportion of the total pores, and its structure is mainly controlled by the abundance of organic matter. The pore structures of macropores and mesopores greatly influence the proportion of desorption gas in shale, while the structure of mini-micropores can control the maximum adsorbed gas volume of shale.